La carne in Tolstoj e Dostoevskij: Slavic Sins of the Flesh di Ronald D. LeBlanc (ENTHYMEMA, 2010)
Recensiamo il saggio di Ronald D. LeBlanc, Slavic Sins of the Flesh: Food, Sex, and Carnal Appetite in Nineteenth-century Russian fiction,  University  of New Hampshire Press, Durham, 2009.
Keywords: Ronald Le Blanc; Tolstoj; Dostoevskij; flesh